A CRITICAL ANALYSIS OF HINDU WOMEN’S RIGHT IN AGRICULTURAL PROPERTY UNDER U.P REVENUE CODE, 2006 IN THE BACKDROP OF GENDER JUSTICE - Rajneeta; Malik, Namita Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Concept of property has been changed over the centuries from the very nature of feudalism to capitalism. Under the Hindu succession amendment act, 2005 if a man dies intestate the daughter will get the same part of his property as his son had. But there is a wide gap in actual ownership of property by women due to some legal loopholes, customary norms and family restrictions. This paper analyses the concept of women’s right to property under Hindu law and UP Revenue law. This paper aims to analyse daughters right under Uttar Pradesh Revenue Code, 2006. Daughters rights under Uttar Pradesh revenue code 2006 are critically analysed in this paper. Women before marriage get a limited succession right in agricultural land of their father. UP Revenue code has changed the scenario of sharing property rights in agricultural land. This paper also highlights the effect of omission of subsection 2 of section 4 of the Hindu succession act, 1956. The inconsistency of central and state laws with respect to legislative power is also highlighted in the paper.